SIMULASI CUTTING AND HOLDING PADA LENGAN EXAVATOR - Wirda Novarika AK; Juner Simbolon (Buletin Utama Teknik, 2019)
In line with the development of science and technology in the modern era now, a lot of simulations that have been created, both in the form of simulation on the screen or in the size of the prototype simulation.The working principle in this simulation tool that uses a DC electric motor drive and Adaptor as the energy supplier. This tool can does movement is holding and cutting. Cutting capacity in this tool is 10 cm on banana tree and requires wiper motor as a driver because it has power 240 Watt = 0,3216 Hp and 120 Watt = 0,1608 Hp Keywords : Maintenance and Repairing, Holding and Cutting